A Call for Cross-Fertilization Among Personality and Personnel Selection Researchers - Lezotte, Daniel V. (Eur J Pers, 2017)
Lievens (2017) makes a case for SJTs in personnel selection, a recommendation with which we agree. In particular, we like the emphasis on branching out from current methodologies and using new techniques such as SJTs not only in I/O or personnel selection research but also in basic personality research. Despite our enthusiasm, we point out some flaws, most notably lack a time dimension to SJTs.